Development of Physics Communication Skill Instruments Based on Local Wisdom for Senior High School Students - Mardikawati, Rizki Ageng; Mundilarto, Mundilarto (Jurnal Pendidikan Indonesia, 2020)
This research aims to develop physics communication skill instruments based on local wisdom for Senior High School Students. The development step was adopted special research for non-test developed by Mardapi (2012). There are ten steps for developing an instrument, such as 1) arrange the specification of the instrument, 2) write the instrument, 3) determine the scale, 4) determine scoring system, 5) recheck the instrument, 6) do the pre-test 7) analyze the instrument, 8) make the final instrument,  9) do the measurement, and 10) analyze the result of the measurement. The communication skills are measured by verbal aspects use the observation sheet through the presentation. Meanwhile, the nonverbal aspect uses the portfolio. This instrument is validated by three experts in evaluation, physics, education, and three teachers of a senior high student. Communication skills consist of five indicators. This study is participated by 33 students of SMA IT Ihsanul Fikri. The content validity was analyzed with the V Aiken formula show that the overall coefficient of each item was valid with the validity coefficient ≥ 0.78. The instrument also reliable with coefficient G Relative ≥ 0.7.